Bibliometric Analysis of the L2 Writing Journal - Jiun-Iung Lei (Widya Mandala Surabaya Catholic University, 2022)
While researchers have begun to clarify the status of L2 writing studies, past bibliometric assessments of L2 writing research may still designate it as a field of applied linguistics. They sought the topic of L2 writing in key databases and journals, retrieved relevant publications, and ran a bibliometric analysis. They might increase the number of papers for review, but they undermine the value and influence of specialist publications, notably the flagship journal of L2 writing. The goal of this study was to undertake a bibliometric analysis of 656 publications published in the Journal of Second Language Writing from 2002 to June 2021, retrieved from WoS and based on HistCite Pro. The HistCite graph marker indicated 30 articles as nodes and 59 combinations of nodes as links. Four out of the five clusters on the citation map originated in 2003, demonstrating that major research issues emerged in the year and took root in subsequent studies.